Implementación y configuración de servidor para mejorar las prestaciones de servicios utilizando ubuntu server en el laboratorio de investigación de Ingeniería de Software de la Carrera de Ingeniería en Informática y Sistemas Computacionales de La Universidad Técnica de Cotopaxi Extensión La Maná, en el año 2017 - Ayala Valiente, Alex Israel (2017)
This research work refers to the implementation and configuration of server to improve the services performance using Ubuntu server in the research laboratory of software engineering of the career of engineering in the last decades, and the increase of the resources of the information nowadays has generated the appearance of different types of servers that allow to maintain a control of all resources of the network. The methodology is oriented in a qualitative and quantitative perspective. In this project a descriptive field, documentary and bibliographical study was applied, a survey was carried out where the research was carried out with a sample of 122 students. Being necessary and fundamental to have a server that allows them to enhance the activities carried out by the department thus improving the teaching – learning of the students of the career. The server has the necessary basic configurations such as MySQL Databases, FTP Server, Web Server, DNS Name Server, and some typical restrictions that are assigned to client computers in the network, if applicable. The results obtained through the implementation of the project and after the server configuration have been demonstrated that the management of the resources in the Laboratory of Software Engineering Research is safe and reliable, with this greatly improving the academic performance of students with the acquisition of new knowledge.